DETERMINANTS OF MEDICATION ADHERENCE AMONG CHRONIC DISEASE PATIENTS IN YOGYAKARTA: STRUCTURAL EQUATION MODELING (PLS-SEM) APPROACH - Octavia, Mega; Al Abrar, Muhammad Azwir; Ghozali , Muhammad Thesa (Universitas Muhammadiyah Ahmad Dahlan Cirebon, 2025)
Chronic diseases are a major global health challenge and remain a leading cause of morbidity and mortality in Indonesia. Sustained adherence to long-term pharmacological therapy is essential but is often suboptimal. This study aimed to analyze the determinants of medication adherence among patients with chronic diseases at RSUD Kota Yogyakarta using structural equation modeling-partial least squares (SEM-PLS). A cross-sectional survey was conducted between January and February 2025 with 120 purposively selected outpatients. Medication adherence was assessed using the Adherence to Refills and Medications Scale (ARMS) and additional questionnaires measuring therapeutic regimens, patient perceptions, socioeconomic factors, and healthcare system attributes. Data were analyzed using SmartPLS 4. The results showed that 74.2% of patients had low adherence and 25.8% had moderate adherence, with none achieving high adherence. SEM-PLS analysis indicated that therapy complexity (?=0.262, p<0.01), patient perception (?=0.381, p<0.01), socioeconomic status (?=0.265, p<0.01), and healthcare system support (?=0.199, p<0.01) were significant predictors, explaining 66% of adherence variance (R²=0.660). In conclusion, medication adherence among patients with chronic diseases in Yogyakarta was low and was strongly influenced by regimen burden, perception, socioeconomic status, and healthcare support. Targeted interventions addressing these factors are essential for improving adherence and long-term health outcomes. Keywords: chronic disease, therapy adherence, ARMS, SEM-PLS, Yogyakarta